Pemanfaatan Bambu Lokal Sebagai Struktur Kandang Ayam Sistem Baterai Di Kelurahan Kelayu Utara Kabupaten Lombok Timur - Fathmah - Mahmud; I Nyoman Merdana; Hariyadi Hariyadi; Ngudiyono Ngudiyono; Ni Nyoman Kencanawati (Universitas Mataram, 2022)
Currently, due to the low production of eggs in Nusa Tenggara Barat Province, most eggs on the market are brought in from other region. Despite it’s huge population, representing 24,6% population of Nusa Tenggara Barat, East Lombok could supply 2% of market demand at most. The high cost of chicken coop construction is one of the main reasons of this low production. Meanwhile, Bamboo is abundant in East Lombok, it’s thrive along Tojang River Bank. Bamboo could be use as substitute material for battery cages. Cost production of battery cages from bamboo is relatively lower than the one made from hardwood, steel, light steel, and baton. Considering accessible substitute materials at lower price are available, the cost production could be reduced. This community service is aiming for local community cognition of local bamboo as low priced material. This community service is implemented by discourse, which done by a number of survey, survey of the community service location, and discourse to give information of how to utilize local bamboo as battery cages material, size of the cages including size of individual cage, gap between column, column’s height, local bamboo as material for frame and purlin, bamboo as economy and environmental friendly material, preservation method, suitable bamboo joint model for battery cages structure. Due to COVID-19, The battery cages constructed in the community service location was evaluated through zoom meeting.